Организация информационного и программного алгоритмического обеспечения компьютерного тренажера - Куник, Е. Г.; Коваленко, А. Н.; Ляшенко, С. А. (ХНУРЭ, 2008)
In the report the urgency of a question of introduction of simulators for ASU TP is noted and experience of application of various kinds of simulators for operators of technological processes in a process industry is considered. A number of features, which are necessary for considering at construction of simulators for training operators, are considered. As an example of ASU TP with successfully planned architecture, the control system metsoDNA firms Metso Automation is offered.
Keywords: компьютерный тренажер